Long-term, regular remote ischemic preconditioning improves endothelial function in patients with coronary heart disease - Liang,Y. (2015)
Remote ischemic preconditioning (RIPre) can prevent myocardial injury. The purpose of this study was to assess the beneficial effects of long-term regular RIPre on human arteries. Forty patients scheduled for coronary artery bypass graft (CABG) surgery were assigned randomly to a RIPre group (n=20) or coronary heart disease (CHD) group (n=20). Twenty patients scheduled for mastectomy were enrolled as a control group. RIPre was achieved by occluding arterial blood flow 5 min with a mercury sphygmomanometer followed by a 5-min reperfusion period, and this was repeated 4 times. The RIPre procedure was repeated 3 times a day for 20 days. In all patients, arterial fragments discarded during surgery were collected to evaluate endothelial function by flow-mediated dilation (FMD), CD34+ monocyte count, and endothelial nitric oxide synthase (eNOS expression). Phosphorylation levels of STAT-3 and Akt were also assayed to explore the underlying mechanisms. Compared with the CHD group, long-term regular RIPre significantly improved FMD after 20 days (8.5±2.4 vs 4.9±4.2%, P<0.05) and significantly reduced troponin after CABG surgery (0.72±0.31 and 1.64±0.19, P<0.05). RIPre activated STAT-3 and increased CD34+ endothelial progenitor cell counts found in arteries. Long-term, regular RIPre improved endothelial function in patients with CHD, possibly due to STAT-3 activation, and this may have led to an increase in endothelial progenitor cells.